Active material layer for all-solid-state lithium secondary battery containing fibrous carbon, and all-solid-state lithium secondary battery

JP7637547B2Active Publication Date: 2025-02-28TEIJIN LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021052647
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-21
Filing Date
2021-03-26
Publication Date
2025-02-28
Estimated Expiration
2040-06-26

AI Technical Summary

Benefits of technology

【0033】 本発明の活物質層は、空隙を有し、且つ繊維形状の導電助剤が配合されているため、充放電時に活物質の膨張収縮による体積変化が生じても、イオン伝導パス及び電子伝導パスが維持される。そのため、イオン伝導性と電子伝導性とを両立させることができる。これにより、反応抵抗を低減させた高出力の全固体リチウム二次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637547000001
    Figure 0007637547000001
  • Figure 0007637547000002
    Figure 0007637547000002
  • Figure 0007637547000003
    Figure 0007637547000003
Patent Text Reader

Abstract

To provide an active material layer for an all-solid lithium secondary battery in which ion conductivity or electron conductivity is hardly reduced even in the case where charge / discharge is repeated.SOLUTION: The present invention relates to an active material layer for an all-solid lithium secondary battery containing at least an active material, a conductive assistant and a solid electrolyte. The active material layer has a cavity. A ratio of the conductive assistant in the active material layer is equal to or more than 0.1 mass% and less than 5.0 mass%. The conductive assistant contains fibrous carbon of which an average fiber diameter ranges from 10 to 900 nm, and a ratio of the fibrous carbon in the conductive assistant is equal to or more than 20 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active material layer for an all-solid-state lithium secondary battery, the active material layer including fibrous carbon, and an all-solid-state lithium secondary battery including the active material layer and a solid electrolyte. [Background technology]

[0002] The active material layer of an all-solid-state lithium secondary battery is composed of at least an active material and a solid electrolyte. A conductive additive is added to the active material layer to improve the electronic conductivity and thereby suppress the increase in resistance. As the conductive additive, fibrous carbon materials that enable long-distance electronic conduction in the active material layer have attracted attention.

[0003] Patent Document 1 proposes an all-solid-state lithium secondary battery that uses a fibrous carbon material as a conductive additive, which enables long-distance electron conduction within the active material layer even with a small amount of addition.

[0004] Patent Document 2 proposes using a combination of fibrous carbon and spherical carbon as a conductive assistant to increase the contact area between the active material and the conductive assistant. Patent Document 2 specifically describes a case where the total content of the conductive assistant, which is the fibrous carbon and the spherical carbon, is 5 mass%.

[0005] In a conventional battery using an electrolyte, in order to ensure lithium ion conduction between the active material and the liquid electrolyte, it is necessary that the active material layer has voids for the electrolyte to penetrate. On the other hand, in the case of an all-solid-state lithium secondary battery, since lithium ions move between the active material and the solid electrolyte, it is considered desirable that the active material layer does not have voids (for example, paragraph 0039 of Patent Document 3). By pressing the electrode with high pressure, the voids can be reduced. This allows the volumetric energy density to be increased. Furthermore, by pressing the electrode with high pressure, the contact area between the active material and the solid electrolyte can be increased, which also contributes to improving battery characteristics such as reducing interface resistance (Patent Document 2). That is, from the viewpoint of improving the volumetric energy density, it is considered preferable that the porosity of the active material layer is closer to 0.

[0006] Patent Document 3 discloses a bulk-type all-solid-state secondary battery that contains specific plastic crystals and lithium salt in the voids of the negative electrode or positive electrode mixture layer and has a void ratio of 0.01 to 20% (paragraph 0039). However, only acetylene black is described as a specific example of the conductive assistant. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2010-262764 A [Patent Document 2] JP 2016-9679 A [Patent Document 3] WO2016 / 157348 publication Summary of the Invention [Problem to be solved by the invention]

[0008] When an electrode is pressed at high pressure in order to reduce the porosity of the active material layer, the active material is likely to be destroyed. Furthermore, an electrode pressed at high pressure is likely to have cracks in the active material layer due to volume changes caused by expansion and contraction of the active material during charging and discharging, which reduces ionic conductivity and electronic conductivity. As a result, battery performance may be reduced. An object of the present invention is to provide an active material layer (hereinafter also simply referred to as "active material layer") of an all-solid-state lithium secondary battery in which ionic conductivity and electronic conductivity are unlikely to decrease even after repeated charging and discharging. [Means for solving the problem]

[0009] The present inventors focused on the voids in the active material layer of the all-solid-state lithium secondary battery. As a result, they found that by having voids, it is possible to suppress the occurrence of cracks in the active material layer even when charging and discharging are repeated with a volume change of the active material. They also found that by using a specific fibrous carbon as a conductive assistant, it is possible to suppress the decrease in electronic conductivity even when charging and discharging are repeated with a volume change of the active material. That is, they found that by having the active material layer have voids and blending a conductive assistant containing fibrous carbon of a specific shape in the active material layer, it is possible to obtain an active material layer in which ionic conductivity and electronic conductivity are unlikely to decrease even when charging and discharging are repeated, and thus completed the present invention.

[0010] That is, the present invention is as follows.

[0011] [1] An active material layer for an all-solid-state lithium secondary battery, comprising at least an active material, a conductive additive, and a solid electrolyte, The active material layer has voids, The proportion of the conductive assistant in the active material layer is 0.1% by mass or more and less than 5.0% by mass, 1. An active material layer for an all-solid-state lithium secondary battery, wherein the conductive assistant contains fibrous carbon having an average fiber diameter of 10 to 900 nm, and the proportion of the fibrous carbon in the conductive assistant is 20 mass % or more.

[0012] [2] The active material layer for an all-solid-state lithium secondary battery according to [1], wherein the active material layer has a porosity of 5.0 vol % or more and 50 vol % or less.

[0013] The invention described in [1] or [2] above is an active material layer for an all-solid-state lithium secondary battery, which contains fibrous carbon of a specific shape as a conductive assistant and has voids. An all-solid-state lithium secondary battery having an active material layer composed of this combination can exhibit excellent battery performance. Although the reason is not necessarily clear, it is thought that the specific fibrous carbon contributes to the formation and maintenance of voids, and the conductive assistant having a specific void and a specific shape can mitigate the effect of volume change of the active material caused by charging and discharging.

[0014] [3] The electrical conductivity of the active material layer in the thickness direction is 1.0 × 10 -3 The active material layer for an all-solid-state lithium secondary battery according to [1] or [2], having a resistivity of 1.5 S / cm or more.

[0015] The invention described in [3] above is an active material layer having enhanced electrical conductivity in the film thickness direction. The electrical conductivity in the film thickness direction is enhanced by orienting fibrous carbon having a predetermined shape in the film thickness direction.

[0016] [4] The active material layer for an all-solid-state lithium secondary battery according to any one of [1] to [3], wherein the volume ratio of the conductive assistant in the active material layer is 0.5 volume % or more and 4.0 volume % or less.

[0017] In the invention described in [4] above, since the conductive assistant contained in the active material layer contains fibrous carbon, high electronic conductivity is achieved even if the amount of the conductive assistant used is small.

[0018] [5] The active material layer for an all-solid-state lithium secondary battery according to any one of [1] to [4], wherein the volume ratio of the fibrous carbon in the active material layer is 0.5 volume % or more and 4 volume % or less.

[0019] The invention described in [5] above contains a predetermined amount of fibrous carbon in the active material layer, and therefore has particularly high electronic conductivity even when the amount of conductive additive used is small.

[0020] [6] The active material layer for an all-solid-state lithium secondary battery according to any one of [1] to [5], wherein the conductive assistant contains the fibrous carbon and spherical particles.

[0021] In the invention described in [6] above, since the active material layer contains fibrous carbon and spherical particles, the fibrous carbon is unlikely to be oriented in one direction in the active material layer, and as a result, the fibrous carbon is easily oriented in the thickness direction of the active material layer.

[0022] [7] The active material layer for an all-solid-state lithium secondary battery according to any one of [1] to [6], wherein the crystallite plane spacing (d002) of the fibrous carbon measured by an X-ray diffraction method is 0.3400 nm or more.

[0023] In the invention described in [7] above, the fibrous carbon contained in the active material layer is unlikely to break, and therefore the electronic conductivity is unlikely to decrease even when the volume of the active material changes due to charging and discharging.

[0024] [8] The active material layer for an all-solid-state lithium secondary battery according to any one of [1] to [7], wherein the coefficient of variation of the effective fiber length of the fibrous carbon is 35% or more and 90% or less.

[0025] In the invention described in [8] above, since fibrous carbon with a long effective fiber length and fibrous carbon with a short effective fiber length coexist in the active material layer, the fibrous carbon with a long effective fiber length can form a long-distance conductive path. In addition, since the fibrous carbon with a short effective fiber length exists, the fibrous carbon with a long effective fiber length is suppressed from being oriented in the in-plane direction.

[0026] [9] The fibrous carbon has the following formula (1): Compression recovery rate (%) = volume resistivity at recovery / volume resistivity at compression × 100 Equation (1) The active material layer for an all-solid-state lithium secondary battery according to any one of [1] to [8], wherein the compression recovery represented by the following formula is 50% or more and 90% or less.

[0027] In the invention described in [9] above, the fibrous carbon contained in the active material layer has elasticity and is not easily broken, so that the electronic conductivity is not easily reduced even by volume changes of the active material caused by charging and discharging.

[0028]

[10] The specific surface area of ​​the conductive assistant is 1 m 2 / g or more 50m 2 / g or less of the active material layer for an all-solid-state lithium secondary battery according to any one of [1] to [9].

[0029] In the invention described in

[10] above, since the specific surface area of ​​the conductive assistant is within a predetermined range, a sufficient contact area with the active material and the conductive assistant can be ensured.

[0030]

[11] The active material layer for an all-solid-state lithium secondary battery according to any one of [1] to

[10] , wherein the active material and the conductive assistant satisfy the following formula (2): Σ(Xe / Re) / Σ(Xa / Ra)<9...Equation (2) Xe: Content (mass%) of the conductive additive contained in the active material layer, Re: Average particle diameter (average fiber diameter) of the conductive assistant contained in the active material layer (μm), Ra: average particle size (μm) of the active material contained in the active material layer, Xa: Content (mass%) of active material in the active material layer

[0031] The invention described in

[11] above specifies the ratio of the total surface area of ​​the conductive additive to the total surface area of ​​the active material. Since the surface of the active material is not completely covered with the conductive additive, a sufficient contact point between the solid electrolyte responsible for ion conduction and the active material is ensured, and good ion conductivity can be ensured.

[0032]

[12] An all-solid-state lithium secondary battery comprising the active material layer according to any one of [1] to

[11] and a solid electrolyte. Effect of the Invention

[0033] The active material layer of the present invention has voids and contains a fibrous conductive assistant, so that even if a volume change occurs due to the expansion and contraction of the active material during charging and discharging, the ionic conductive path and the electronic conductive path are maintained. Therefore, both ionic conductivity and electronic conductivity can be achieved. This makes it possible to provide a high-output all-solid-state lithium secondary battery with reduced reaction resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] 1. Active material layer for all-solid-state lithium secondary batteries The active material layer for an all-solid-state lithium secondary battery of the present invention may be either a positive electrode active material layer or a negative electrode active material layer of an all-solid-state lithium secondary battery. This active material layer is composed of at least an active material, a solid electrolyte, and a conductive assistant. The conductive assistant contains at least fibrous carbon.

[0035] The active material layer has voids. The porosity is preferably 5.0% by volume or more and 50% by volume or less. When the porosity is in this range, even if charge-discharge cycles accompanied by volume changes of the active material are repeated, the occurrence of cracks in the active material layer is particularly suppressed. By using an active material layer having such voids, it is possible to configure a high-output all-solid-state lithium secondary battery with high electronic conductivity and ionic conductivity. The lower limit of the porosity is preferably 7.0% by volume, preferably 9.0% by volume, preferably 10% by volume, more preferably 11% by volume, even more preferably 12% by volume, even more preferably 15% by volume, and particularly preferably 18% by volume. The upper limit of the porosity is preferably 48% by volume, more preferably 45% by volume, even more preferably 42% by volume, even more preferably 37% by volume, and particularly preferably 30% by volume.

[0036] The porosity of this active material layer can be adjusted by controlling the average fiber diameter and average effective fiber length of the fibrous carbon described later, as well as the material, size, and content of the positive electrode or negative electrode active material used, and further the molding conditions of the pressure molding that is performed as necessary when forming the active material layer.

[0037] The method for calculating the porosity is not particularly limited, but examples include a method of calculating the porosity based on the true density and density of the active material layer based on the following formula (3), and a method of calculating the porosity from a three-dimensional image obtained by tomography such as X-ray CT. Porosity (volume%) = (true density - density of active material layer) / true density × 100 Equation (3)

[0038] When calculating based on formula (3), the true density and the apparent density of the active material layer are each measured. The true density can be measured, for example, by calculating from the true density and mass ratio of each material constituting the active material layer, or by measuring using a gas phase substitution method (pycnometer method) or a liquid phase method (Archimedes method) after pulverizing the active material layer. The apparent density of the active material layer can be calculated, for example, from the mass and volume of the active material layer using the following formula (4). Apparent density of active material layer=mass of active material layer / (film thickness of active material layer×area) Equation (4)

[0039] The electrical conductivity of the active material layer in the thickness direction is 1.0×10 -3 S / cm or more is preferable, and 5.0×10 -3 More preferably, it is 1.0×10 -2 More preferably, it is 1.6×10 S / cm or more. -2 It is particularly preferable that the electrical conductivity is 1.0 S / cm or more. Such an electrical conductivity can be achieved by including a specific fibrous carbon as a conductive assistant.

[0040] (1) Positive electrode active material layer The positive electrode active material layer of the present invention contains at least a positive electrode active material, a solid electrolyte, and a conductive assistant, and may further contain a binder and the like.

[0041] As the positive electrode active material, a conventionally known material can be used. For example, a lithium-containing metal oxide capable of absorbing and releasing lithium ions is suitable. As the lithium-containing metal oxide, a composite oxide containing lithium and at least one element selected from the group consisting of Co, Mg, Mn, Ni, Fe, Al, Mo, V, W, Ti, etc. can be mentioned.

[0042] Specifically, Li x CoO2, Li x NiO2, Li x MnO2, Li x Co a Ni 1- aO2, Li x Co b V 1-b O z , Li x Co b Fe 1-b O2, Li x Mn2O4, Li x Mn c Co 2-c O4, Li x Mn c Ni 2-c O4, Li x Mn c V 2-c O4, Li x Mn c Fe 2-c O4, Li x Ni a Mn d Co 1-a―d O2, Li x Ni a Co d Al 1-a―d O2, (wherein x=0.02 to 1.2, a=0.1 to 0.9, b=0.8 to 0.98, c=1.2 to 1.96, d=0.1 to 0.9, z=2.01 to 2.3), etc. A preferred lithium-containing metal oxide is Li x CoO2, Li x NiO2, Li x MnO2, Li x Co a Ni 1-a O2, Lix Mn2O4, Li x Mn c Co 2-c O4, Li x Mn c Ni 2-c O4, Li x Co b V 1-b O z , Li x Ni a Mn d Co 1-a―d O2, Li x Ni a Co d Al 1-a―d O2 (wherein x, a, b, c, d, and z are the same as above). The positive electrode active material may be used alone or in combination of two or more. The value of x is the value before the start of charging and discharging, and varies with charging and discharging.

[0043] The surface of the positive electrode active material may be covered with a coating layer. The coating layer can suppress the reaction between the positive electrode active material and the solid electrolyte (particularly the sulfide solid electrolyte). Examples of the coating layer include Li-containing oxides such as LiNbO3, Li3PO4, and LiPON. The average thickness of the coating layer is, for example, 1 nm or more. On the other hand, the average thickness of the coating layer is, for example, 20 nm or less, and may be 10 nm or less.

[0044] The average particle size of the positive electrode active material is preferably 20 μm or less, more preferably 0.05 to 15 μm, and even more preferably 1 to 12 μm. If the average particle size exceeds 20 μm, the efficiency of the charge / discharge reaction under a large current may decrease.

[0045] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably 30 to 99 mass%, more preferably 40 to 95 mass%, and even more preferably 50 to 90 mass%. If it is less than 30 mass%, it may be difficult to apply it to power sources that require high energy density. If it exceeds 99 mass%, the content of materials other than the positive electrode active material may decrease, and the performance of the positive electrode active material layer may be reduced.

[0046] The content of the solid electrolyte in the positive electrode active material layer is not particularly limited, but is preferably 5 to 60 mass%, more preferably 10 to 50 mass%, and even more preferably 20 to 40 mass%. If it is less than 5 mass%, the ion conductivity of the positive electrode active material layer may be insufficient. If it exceeds 60 mass%, the content of the positive electrode active material becomes small, and it may be difficult to apply it to power source applications that require high energy density.

[0047] The positive electrode active material layer may contain a small amount of a binder as long as the amount does not impair the electronic conductivity and the ionic conductivity.

[0048] The thickness of the positive electrode active material layer is usually 10 to 1000 μm.

[0049] (2) Negative electrode active material layer The negative electrode active material layer constituting the all-solid-state lithium secondary battery of the present invention contains at least a negative electrode active material, and may also contain a solid electrolyte, a conductive assistant, a binder, and the like.

[0050] As the negative electrode active material, a conventionally known material can be selected and used. For example, Li metal, carbon material, lithium titanate (Li4Ti5O 12 Any one of Si, Sn, In, Ag and Al, or an alloy or oxide containing at least one of them can be used. Among these, Li metal is preferred from the viewpoint of increasing the energy density.

[0051] Carbon materials are widely used as negative electrode active materials other than Li metal, including natural graphite, artificial graphite produced by heat treatment of petroleum- or coal-based coke, hard carbon produced by carbonizing resin, and mesophase pitch-based carbon materials.

[0052] As a carbon material selected as the negative electrode active material of an all-solid-state battery, hard carbon is preferable because the crystal layer spacing is wide and the expansion and contraction during charging and discharging is relatively small. Hard carbon has a structure in which fine crystalline graphene layers are arranged without regularity, and lithium ions are absorbed by the insertion of lithium ions into the graphene layers and the aggregation of lithium in the spaces formed between the graphene layers (lithium metallization).

[0053] When natural graphite or artificial graphite is used, it is preferable that the interplanar spacing d(002) of the (002) plane of the graphite structure by powder X-ray diffraction is in the range of 0.335 to 0.337 nm from the viewpoint of increasing the battery capacity. Natural graphite refers to a graphitic material that occurs naturally as an ore. Depending on its appearance and properties, natural graphite is divided into two types: scaly graphite with a high degree of crystallinity and earthy graphite with a low degree of crystallinity. Scaly graphite is further divided into flake graphite with a leaf-like appearance and scaly graphite with a lump-like appearance. There are no particular limitations on the place of origin, properties, or type of natural graphite that becomes the graphitic material. In addition, natural graphite or particles produced from natural graphite as a raw material may be heat-treated before use.

[0054] Artificial graphite refers to graphite and graphitic materials that are close to perfect crystals of graphite, which are widely made by artificial methods. A typical example is graphite obtained by using tar and coke obtained from the residues of coal dry distillation and crude oil distillation as raw materials, and going through a baking process at about 500 to 1000 °C and a graphitization process at 2000 °C or higher. Kish graphite, which is obtained by reprecipitating carbon from molten iron, is also a type of artificial graphite.

[0055] The use of an alloy containing at least one of Si and Sn in addition to a carbon material as the negative electrode active material is effective in that the electric capacity can be reduced compared to the case where Si and Sn are used alone or the case where the oxides of each are used. Among these, Si-based alloys are preferable. Examples of Si-based alloys include alloys of at least one element selected from the group consisting of B, Mg, Ca, Ti, Fe, Co, Mo, Cr, V, W, Ni, Mn, Zn, and Cu, and Si. Specifically, at least one element selected from the group consisting of SiB4, SiB6, Mg2Si, Ni2Si, TiSi2, MoSi2, CoSi2, NiSi2, CaSi2, CrSi2, Cu5Si, FeSi2, MnSi2, VSi2, WSi2, and ZnSi2 can be mentioned.

[0056] In the active material layer for an all-solid-state lithium secondary battery of the present invention, the above-mentioned materials may be used alone or in combination of two or more as the negative electrode active material.

[0057] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is preferably 30 to 100 mass%, more preferably 40 to 99 mass%, and even more preferably 50 to 95 mass%. If it is less than 30 mass%, it may be difficult to apply the negative electrode active material to power sources that require high energy density.

[0058] The content of the solid electrolyte in the negative electrode active material layer is not particularly limited, but is preferably 0 to 60 mass%, more preferably 5 to 50 mass%, and even more preferably 10 to 40 mass%. If it exceeds 60 mass%, the content of the positive electrode active material becomes small, and it may become difficult to apply it to power source applications that require high energy density.

[0059] The negative electrode active material layer may contain a small amount of a binder as long as the amount does not impair the electronic conductivity and the ionic conductivity.

[0060] The thickness of the negative electrode active material layer is usually 1 to 1000 μm.

[0061] (3) Solid electrolyte The solid electrolyte used in the present invention can be selected from conventionally known materials. For example, sulfide-based solid electrolytes, oxide-based solid electrolytes, hydride-based solid electrolytes, and polymer electrolytes can be used. In the present invention, it is preferable to use a sulfide-based solid electrolyte because it has high lithium ion conductivity.

[0062] A specific example of the sulfide-based solid electrolyte is a sulfide-based solid electrolyte (Li-AS) consisting of Li, A, and S. In the sulfide-based solid electrolyte Li-AS, A is at least one selected from the group consisting of P, Ge, B, Si, Sb, and I. A specific example of such a sulfide-based solid electrolyte Li-AS is Li7P3S 11 , 70Li2S-30P2S5, LiGe 0.25 P 0.75 S4, 75Li2S-25P2S5, 80Li2S-20P2S5, Li 10 GeP2S 12 , Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 , Li2S-SiS2, Li6PS5Cl, etc., and Li7P3S in particular is preferred due to its high ionic conductivity. 11 is preferred.

[0063] Specific examples of hydride-based solid electrolytes include complex hydrides of lithium borohydride, such as LiBH4-LiI complex hydrides, LiBH4-LiNH2 complex hydrides, LiBH4-P2S5, and LiBH4-P2I4.

[0064] The solid electrolytes may be used alone or in combination of two or more kinds, if necessary.

[0065] (4) Conductive additives The conductive assistant contained in the active material layer of the present invention contains fibrous carbon, which will be described later. In addition to the fibrous carbon, a carbon-based conductive assistant in a form other than fiber may also be contained.

[0066] The proportion of the conductive assistant contained in the active material layer is 0.1% by mass or more and less than 5% by mass. The lower limit of the proportion of the conductive assistant is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, even more preferably 1.2% by mass or more, and particularly preferably 1.5% by mass or more. The upper limit of the proportion of the conductive assistant is preferably 4.5% by mass or less, more preferably 4.0% by mass or less, even more preferably 3.5% by mass or less, even more preferably 3.0% by mass or less, and particularly preferably 2.5% by mass or less. When the proportion of the conductive assistant is in the above range, the balance between the electronic conductivity and the lithium ion conductivity is good, the rate characteristic value is high, and the reaction resistance value can be reduced. In addition, since the amount of the conductive assistant in the active material layer is small, the amount of the active material can be increased.

[0067] The conductive assistant contains at least fibrous carbon. From the viewpoint of increasing the electronic conductivity of the active material layer, the proportion of fibrous carbon in the conductive assistant is preferably 20% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 85% by mass or more, and particularly preferably 90% by mass or more. It may also be 100% by mass. And, it is preferably 99% by mass or less.

[0068] The specific surface area of ​​the conductive additive is 1m 2 / g or more 50m 2 / g or less. 2 If it is less than 1 / g, it may be difficult to ensure contact between the active material and the conductive additive, and an electron conductive path may not be sufficiently formed. On the other hand, if the specific surface area is too large, it may obstruct the ion conduction path. 2 If the specific surface area exceeds 2 m / g, the conductive additive covers the surface of the active material, reducing the number of contact points between the active material and the solid electrolyte that is responsible for ion conduction, which may inhibit ion conduction. 2 / g or more, and 2 / g or more is more preferable, and 5m 2 / g or more is more preferable, 2 / g or more. The upper limit of the specific surface area is 40 m 2 / g or less, and 2 / g or less is more preferable, and 25m 2 / g or less is more preferable, 2 It is particularly preferable that the molecular weight is not more than 1 / g.

[0069] The active material and the conductive assistant contained in the active material layer preferably satisfy the following formula (2). Σ(Xe / Re) / Σ(Xa / Ra)<9...Equation (2) Xe: Content (mass%) of the conductive additive contained in the active material layer, Re: Average particle diameter (average fiber diameter) of the conductive assistant contained in the active material layer (μm), Ra: average particle size (μm) of the active material contained in the active material layer, Xa: Content (mass%) of active material in the active material layer

[0070] Since the average particle diameter (fiber diameter) of the conductive assistant is inversely proportional to the specific surface area of ​​the conductive assistant, Xe / Re is proportional to the total surface area of ​​the conductive assistant. When the conductive assistant contains both fibrous carbon and spherical carbon, the respective Xe / Re values ​​are calculated and added together to obtain Σ(Xe / Re), which is proportional to the specific surface area of ​​the conductive assistant. Similarly, the average particle diameter: R of the active material is inversely proportional to the specific surface area of ​​the active material, so Σ(Xa / Ra) is proportional to the total surface area of ​​the active material. Therefore, the left side of equation (2) is proportional to (total surface area of ​​conductive assistant) / (total surface area of ​​active material). The right side of formula (2) is preferably 8, more preferably 7, more preferably 6, more preferably 5, more preferably 4, more preferably 3, and particularly preferably 2.5. When Σ(Xe / Re) / Σ(Xa / Ra) is 9 or more, the total surface area of ​​the conductive assistant becomes excessive relative to the total surface area of ​​the active material, and the contact points between the solid electrolyte responsible for ion conduction and the active material are reduced, which may inhibit ion conduction.

[0071] It is preferable that the contents of the active material and conductive assistant contained in the active material layer, the specific surface area of ​​the conductive assistant, and the average particle size of the active material satisfy the following formula (3). Σ(σ×Xe) / Σ(Xa / Ra)<20...Equation (3) σ: Specific surface area of ​​the conductive additive contained in the active material layer (m 2 / g), Xe: Content (mass%) of the conductive additive contained in the active material layer, Ra: average particle size (μm) of the active material contained in the active material layer, Xa: Content (mass%) of active material in the active material layer

[0072] Since the average particle size of the active material, Ra, is inversely proportional to the specific surface area of ​​the active material, Σ(Xa / Ra) is proportional to the total surface area of ​​the active material. On the other hand, Σ(σ×Xe) is proportional to the total surface area of ​​the conductive additive. Therefore, the left side of equation (3) is proportional to (total surface area of ​​the conductive additive) / (total surface area of ​​the active material). The right side of formula (3) is preferably 15, more preferably 13, more preferably 12, more preferably 10, more preferably 8, more preferably 6, more preferably 5, and particularly preferably 4. When Σ(σ×Xe) / Σ(Xa / Ra) is 20 or more, the total surface area of ​​the conductive assistant becomes excessive relative to the total surface area of ​​the active material, and the number of contact points between the solid electrolyte responsible for ion conduction and the active material decreases, which may inhibit ion conduction.

[0073] The ratio of fibrous carbon contained in the active material layer is preferably 0.1% by mass or more and 4.0% by mass or less. The lower limit of the ratio of fibrous carbon is more preferably 0.5% by mass or more, even more preferably 1.0% by mass or more, even more preferably 1.2% by mass or more, even more preferably 1.5% by mass or more, and particularly preferably 1.8% by mass or more. The upper limit of the ratio of fibrous carbon is more preferably 3.5% by mass or less, even more preferably 3.0% by mass or less, even more preferably 2.5% by mass or less, and particularly preferably 2.3% by mass or less.

[0074] In the active material layer of the present invention, the volume ratio of the conductive assistant is important in consideration of the formation of a conductive path in the active material layer. The active material layer has voids. Therefore, the numerical values ​​of the volume ratio of the conductive assistant in the active material layer are all apparent volume ratios taking into account the voids in the active material layer. The volume ratio of the conductive assistant in the active material layer is preferably 0.5 volume% or more and 4.0 volume% or less. The lower limit of the volume ratio of the conductive assistant is more preferably 1.0 volume% or more, even more preferably 1.2 volume% or more, and particularly preferably 1.5 volume% or more. The upper limit of the volume ratio of the conductive assistant is more preferably 3.5 volume% or less, even more preferably 3.0 volume% or less, even more preferably 2.5 volume% or less, even more preferably 2.2 volume% or less, and particularly preferably 2.0 volume% or less. If the volume ratio of the conductive assistant is less than 0.5% by volume, the conductivity of the active material layer becomes insufficient, and the battery performance may not be improved sufficiently. If the volume ratio of the conductive assistant exceeds 4.0% by volume, the conductive assistant is excessive, and the active material is covered with the conductive assistant, making it difficult to secure a contact point between the active material and the solid electrolyte. As a result, the conductivity of lithium ions decreases, and the battery performance may not be sufficiently improved. In addition, the amount of the conductive assistant increases, and the amount of the active material in the active material layer decreases relatively.

[0075] The volume ratio of the fibrous carbon in the active material layer is preferably 0.5% by volume or more and 4.0% by volume or less. The active material layer has voids. Therefore, the numerical value of the volume ratio of the fibrous carbon in the active material layer is an apparent volume ratio taking into account the voids in the active material layer. The lower limit of the volume ratio of the fibrous carbon is more preferably 1.0% by volume or more, even more preferably 1.2% by volume or more, and particularly preferably 1.5% by volume or more. The upper limit of the volume ratio of the fibrous carbon is more preferably 3.5% by volume or less, even more preferably 3.0% by volume or less, even more preferably 2.5% by volume or less, even more preferably 2.2% by volume or less, and particularly preferably 2.0% by volume or less. If the volume ratio of the fibrous carbon is less than 0.5% by volume, the conductivity of the active material layer becomes insufficient, and the battery performance may not be sufficiently improved. If the volume ratio of the fibrous carbon exceeds 4.0% by volume, the amount of the fibrous carbon is increased, and as a result, the amount of the active material in the active material layer is relatively reduced. In addition, if the amount of fibrous carbon is excessive, the active material may be covered with the fibrous carbon, making it difficult to secure a contact point between the active material and the solid electrolyte, resulting in a decrease in the conductivity of lithium ions and a failure to sufficiently improve the battery performance.

[0076] (4-1) Fibrous carbon The fibrous carbon contained in the active material layer of the present invention is not particularly limited as long as it exerts the effects of the present invention, and representative examples include natural graphite, artificial graphite produced by heat treating petroleum-based and coal-based coke, non-graphitizable carbon, graphitizable carbon, carbon fiber, carbon nanotubes (CNT), and vapor-grown carbon fiber (VGCF (registered trademark)).

[0077] In the fibrous carbon of the present invention, the distance (d002) between adjacent graphite sheets measured by wide-angle X-ray measurement is preferably 0.3400 nm or more, more preferably 0.3410 nm or more, and even more preferably 0.3420 nm or more. Moreover, d002 is preferably 0.3450 nm or less, and more preferably 0.3445 nm or less. When d002 is 0.3400 nm or more, the fibrous carbon is less likely to become brittle. Therefore, during processing such as disintegration or preparation of a kneaded slurry, the fibers are less likely to break and the fiber length is maintained. As a result, it becomes easier to form a long-distance conductive path. In addition, the conductive path is easily maintained by following the volume change of the active material accompanying the charge and discharge of the all-solid-state lithium secondary battery.

[0078] The crystallite size (Lc002) of the fibrous carbon of the present invention measured by wide-angle X-ray measurement is preferably 50 nm or less, more preferably 30 nm or less. The larger the crystallite size (Lc002), the higher the crystallinity and the better the electrical conductivity. However, when the crystallite size (Lc002) is small, the fibrous carbon is less likely to become brittle. Therefore, the fibers are less likely to break during processing such as crushing or preparing a kneaded slurry, and the fiber length is maintained. As a result, it is easy to form a long-distance conductive path. In addition, the conductive path is easily maintained by following the volume change of the active material accompanying the charge and discharge of the all-solid-state lithium secondary battery. In the present invention, the crystallite size (Lc002) refers to a value measured according to Japanese Industrial Standard JIS R 7651 (2007 edition) "Method of measuring lattice constant and crystallite size of carbon materials."

[0079] The average fiber diameter of the fibrous carbon used in the present invention is preferably 10 nm or more and 900 nm or less. The upper limit is preferably 600 nm or less, more preferably 500 nm or less, even more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is preferably 50 nm or more, more preferably 100 nm or more, even more preferably 150 nm or more, even more preferably 200 nm or more, and particularly preferably more than 200 nm. Fibrous carbon with an average fiber diameter of less than 10 nm has a very small bulk density and is poor in handleability. In addition, when an active material layer is formed, the strength of the active material layer tends to decrease. In addition, fibrous carbon with an average fiber diameter of less than 10 nm has a large specific surface area, and covers the surface of the active material in the active material layer. As a result, the contact points between the solid electrolyte and the active material are reduced, which leads to the inhibition of the formation of an ion conduction path. Fibrous carbon with an average fiber diameter of more than 900 nm is prone to gaps between the fibers in the active material layer, which may make it difficult to increase the density of the active material layer.

[0080] The specific surface area of ​​fibrous carbon is 1m 2 / g or more 50m 2 / g or less is preferable. The upper limit is 40m 2 / g or less is preferable, and 30m 2 / g or less is more preferable, and 25m 2 / g or less is more preferable, and 20m 2 / g or less is particularly preferable. The lower limit is 1m 2 / g or more is preferable, and 2m 2 / g or more is more preferable, and 3m 2 / g or more is more preferable, and 5m 2 / g or more is even more preferable, 2 / g or more is particularly preferred.

[0081] The fibrous carbon used in the present invention has high electrical conductivity even when the packing density is low. The fibrous carbon having high electrical conductivity even when the packing density is low can impart electrical conductivity at a lower addition concentration.

[0082] Specifically, the packing density is 0.8 g / cm 3 The powder volume resistivity when filled is 4.00×10 -2 It is preferable that the resistance is Ω·cm or less, and 3.00×10 -2 It is more preferable that the resistivity is 4.00×10 Ω·cm or less. -2 If the electrical conductivity exceeds Ω·cm, the amount of fibrous carbon required to improve the electrical conductivity will increase, which is not desirable. There is no particular lower limit, but the lower limit is generally about 0.0001 Ω·cm.

[0083] Also, the packing density is 0.5g / cm 3 The powder volume resistivity when filled is preferably 0.10 Ω·cm or less, more preferably 0.08 Ω·cm or less. If it exceeds 0.10 Ω·cm, the amount of fibrous carbon required to improve the conductivity becomes large, which is not preferable. The lower limit is not particularly limited, but is generally about 0.0001 Ω·cm.

[0084] The average effective fiber length of the fibrous carbon used in the present invention is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, even more preferably 40 μm or more, and particularly preferably 50 μm or more. The average effective fiber length is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 120 μm or less. When an active material layer is produced using fibrous carbon with an average effective fiber length of less than 10 μm, the formation of a conductive path in the active material layer is likely to be insufficient, and the resistance value in the thickness direction of the active material layer may not be sufficiently reduced. When an active material layer is produced using fibrous carbon with an average effective fiber length of more than 200 μm, the fibrous carbon is likely to be oriented in the in-plane direction in the active material layer. As a result, it may be difficult to form a conductive path in the thickness direction.

[0085] In the present invention, the effective fiber length of the fibrous carbon is defined as the length of the longest line segment whose both ends are in contact with the single fibrous carbon. In other words, it is the maximum linear distance that the single fibrous carbon can conduct electricity. That is, when the fibrous carbon has a completely linear structure, the effective length is approximately equal to the fiber length. When the fibrous carbon has a branched structure or is curled, it is the length of the maximum line segment connecting two points on the single fibrous carbon.

[0086] The coefficient of variation (CV value) of the effective fiber length in the fibrous carbon used in the present invention is preferably 20% or more, more preferably 30% or more, even more preferably 35% or more, and particularly preferably 40% or more. Furthermore, the coefficient of variation (CV value) of the effective fiber length in the fibrous carbon used in the present invention is preferably 90% or less, more preferably 85% or less. By having the coefficient of variation of the effective fiber length of 20% or more and 90% or less, a state is created in which fibrous carbon with a long effective fiber length and fibrous carbon with a short effective fiber length coexist. Therefore, the fibrous carbon with a long effective fiber length can efficiently form a long-distance conductive path in the active material layer, and the fibrous carbon with a short effective fiber length can ensure a contact point with the active material. Furthermore, the method for forming the active material layer is not particularly limited. For example, when a method is used in which each material constituting the active material layer is dispersed in a liquid and then coated and dried, the effect of fibrous carbon having a short effective fiber length in inhibiting fibrous carbon having a long effective fiber length from orienting in the in-plane direction can be enhanced, and a conductive path can be efficiently formed in the film thickness direction.

[0087] The fibrous carbon used in the present invention has an average effective fiber length (A) and an average fiber length (B) that satisfy the following formula (1): 0.500 < A / B < 0.900...Equation (1) It is preferable that the lower limit of A / B is 0.550, more preferably 0.600, and particularly preferably 0.650. It is preferable that the upper limit of A / B is 0.850, more preferably 0.800, and particularly preferably 0.750.

[0088] The fibrous carbon used in the present invention has a smaller average effective fiber length (A) than the average fiber length (B). That is, most of the fibrous carbon has a slightly curved shape rather than a completely straight shape. The fibrous carbon having such a shape is suppressed from being oriented in the in-plane direction in the active material layer. That is, since the fibrous carbons are in contact with each other and have a curved shape, the fibrous carbon is randomly dispersed without being oriented in a fixed direction. Therefore, a sufficient amount of fibrous carbon is oriented in the thickness direction of the active material layer. As a result, a large number of long-distance conductive paths can be formed in the thickness direction of the active material layer.

[0089] The fibrous carbon having such a shape can be produced by passing through resin composite fibers produced under predetermined conditions and baking at a predetermined temperature in the process for producing the fibrous carbon.

[0090] The average aspect ratio of the fibrous carbon, that is, the ratio (L / D) of the average effective fiber length (L) to the average fiber diameter (D), is preferably 80 or more, more preferably 100 or more, and particularly preferably 200 or more. By making the average aspect ratio 80 or more, when an active material layer is manufactured using the fibrous carbon, a conductive path is efficiently formed in the active material layer by the fibrous carbon. As a result, the cycle characteristics of a battery manufactured including this active material layer can be improved. In addition, by making the average aspect ratio 80 or more, the mechanical strength of the composite layer can be increased, and even if the active material expands and contracts during charging and discharging and stress is applied to the active material layer, the active material layer can be prevented from cracking. When the average aspect ratio is less than 80, when an active material layer is produced using this fibrous carbon, the formation of a conductive path by the fibrous carbon in the active material layer is likely to be insufficient, and the resistance value in the thickness direction of the active material layer may not be sufficiently reduced. In addition, since the mechanical strength of the active material layer is insufficient, cracks are likely to occur in the active material layer when stress is applied to the composite layer during volume change of the active material due to charging and discharging. The upper limit of the average aspect ratio is 10000, preferably 1000 or less, and more preferably 800 or less. When the aspect ratio exceeds 10000, the fibrous carbon may be entangled with each other to form aggregates, which causes a bias in the electronic conductive path in the active material layer and causes non-uniform charging and discharging reactions, which may result in insufficient performance of the all-solid-state battery or deterioration of the all-solid-state battery.

[0091] The fibrous carbon used in the present invention preferably has a compression recovery represented by the following formula (1) of 50% or more and 90% or less. Compression recovery rate (%) = volume resistivity at recovery / volume resistivity at compression × 100 Equation (1)

[0092] Specifically, the compression recovery rate (%) refers to the ratio (%) of the change in volume resistivity when a pressure is applied to the fibrous carbon from 0.1 MPa to 1.0 MPa to the change in volume resistivity when the pressure is reduced from 1.0 MPa to 0.1 MPa.

[0093] If the compression recovery is within this range, the fibrous carbon flexibly follows the volume expansion and contraction of the active material due to repeated charge and discharge cycles, maintaining the voids and being less likely to break. Therefore, the conductive path formed in the active material layer is sufficiently maintained. In addition, due to the excellent elasticity of the fibrous carbon, the mechanical strength of the active material layer can be increased, and the ion conductive path formed by the solid electrolyte can be sufficiently maintained. As a result, an all-solid-state lithium secondary battery with high cycle characteristics can be provided.

[0094] The lower limit of the compression recovery rate is more preferably 53%, further preferably 56%, and particularly preferably 58%. The upper limit of the compression recovery rate is more preferably 87%, further preferably 84%, and particularly preferably 78%.

[0095] The fibrous carbon used in the present invention is preferably substantially free of branching. Here, substantially free of branching means that the degree of branching is 0.01 pieces / μm or less. Branching refers to a granular portion in which the fibrous carbon is bonded to other fibrous carbon at a location other than the terminal portion, and refers to the main axis of the fibrous carbon being branched in the middle, and the main axis of the fibrous carbon having a branched sub-axis. As a branched fibrous carbon, for example, vapor-phase grown (vapor-phase method) carbon fiber (for example, VGCF (registered trademark) manufactured by Showa Denko KK) produced by a vapor phase method in which a hydrocarbon such as benzene is vaporized in a high-temperature atmosphere in the presence of a metal such as iron as a catalyst is known. Since the fibrous carbon in the present invention has a substantially linear structure, it has better dispersibility than fibrous carbon having branches, and is easy to form a long-distance conductive path.

[0096] Here, the degree of branching of the fibrous carbon used in the present invention means a value measured from a photograph taken at a magnification of 5,000 times by a field emission scanning electron microscope.

[0097] In addition, this fibrous carbon may have a fibrous form as a whole, and includes, for example, carbon having an aspect ratio less than the preferred range above that is in contact or bonded together to form an integrated fibrous shape (for example, carbon globules strung together like beads, or at least one or more extremely short fibers connected by fusion or the like).

[0098] The fibrous carbon of the present invention preferably does not substantially contain metal elements. Specifically, the total content of metal elements is preferably 50 ppm or less, more preferably 30 ppm or less, and even more preferably 20 ppm or less. When the content of metal elements exceeds 50 ppm, the catalytic action of the metal easily deteriorates the battery. In the present invention, the content of metal elements means the total content of Li, Na, Ti, Mn, Fe, Ni, and Co. In particular, the content of Fe is preferably 5 ppm or less, more preferably 3 ppm or less, and even more preferably 1 ppm or less. When the content of Fe exceeds 5 ppm, it is not preferable because the battery is easily deteriorated.

[0099] The fibrous carbon used in the present invention preferably has hydrogen, nitrogen and ash content of 0.5% by mass or less, more preferably 0.3% by mass or less, in the fibers. When the hydrogen, nitrogen and ash content of the fibrous carbon are each 0.5% by mass or less, structural defects in the graphite layer are further suppressed, and side reactions in the battery can be suppressed, which is preferable.

[0100] Among the fibrous carbons of the present invention, those other than carbon nanotubes (CNTs) and vapor-grown carbon fibers (VGCF (registered trademark)) have particularly excellent dispersibility in the active material layer. The reason for this is unclear, but it is thought that they have the above-mentioned structure, that they use artificial graphite, non-graphitizable carbon, and graphitizable carbon produced by heat treating natural graphite, petroleum-based and coal-based coke, as raw materials, and that they are produced through resin composite fibers in the manufacturing process. Since they have excellent dispersibility in the active material layer even without containing spherical particles, they can form long-distance conductive paths, and it is thought that they can exhibit excellent battery performance with a small content.

[0101] The fibrous carbon of the present invention may have a porous or hollow structure, but in the manufacturing process of the fibrous carbon, it is preferable to use a resin composite fiber obtained by melt blend spinning. Therefore, the fibrous carbon of the present invention is substantially solid, has a basically smooth surface, and preferably has a linear structure without branches as described above.

[0102] The surface of the carbon fiber used in the present invention may be modified chemically or physically. The modifying substance and the type of modification are not particularly limited, and a suitable one may be selected according to the purpose of the modification.

[0103] The inventors believe that the fibrous carbon used in the present invention contributes to the formation of a conductive path in the thickness direction in the active material layer, functions as a reinforcing filler to increase the mechanical strength of the active material layer, and functions to form voids (spaces) with a specific porosity in the active material layer and maintain the voids. That is, by using the fibrous carbon, the mechanical strength of the active material layer is improved, and a predetermined void is formed in the active material layer and the voids are maintained so that they do not disappear, thereby exhibiting cushioning properties contributed by the voids and cushioning properties based on the flexibility and elasticity of the fibrous carbon. As a result, even if a volume change occurs due to the expansion and contraction of the active material during charging and discharging, the electronic conductivity and ionic conductivity are maintained at a high level, and it is presumed that the performance of the all-solid-state lithium secondary battery is improved.

[0104] The fibrous carbon used in the present invention can be produced, for example, by the following method. First, a mesophase pitch composition is prepared in which mesophase pitch is dispersed in a thermoplastic resin. Next, this mesophase pitch composition is molded in a molten state into a filament or film. Spinning is particularly preferred. By spinning, the mesophase pitch dispersed in the thermoplastic resin is stretched inside the thermoplastic resin, and the mesophase pitch composition is fibrous to obtain a resin composite fiber. This resin composite fiber has a sea-island structure in which the thermoplastic resin is the sea component and the mesophase pitch is the island component.

[0105] The resin composite fiber is then contacted with an oxygen-containing gas to stabilize the mesophase pitch, thereby obtaining a resin composite stabilized fiber. The resin composite stabilized fiber has a sea-island structure with a thermoplastic resin as a sea component and stabilized mesophase pitch as an island component.

[0106] Next, the thermoplastic resin, which is the sea component of the resin composite stabilized fiber, is removed and separated to obtain a fibrous carbon precursor.

[0107] Furthermore, this fibrous carbon precursor is heated at a high temperature to obtain ultrafine carbon fibers, which are fibrous carbon.

[0108] That is, the fibrous carbon used in the present invention can be produced through the following steps. (1) a molding step of forming a mesophase pitch composition comprising a thermoplastic resin and mesophase pitch in a molten state to convert the mesophase pitch into fiber to obtain a resin composite fiber; (2) a stabilization step of contacting the resin composite fiber with an oxygen-containing gas to stabilize the mesophase pitch and obtain a resin composite stabilized fiber; (3) a removal step of removing the thermoplastic resin from the resin composite stabilized fiber to obtain a fibrous carbon precursor; (4) A high-temperature heating step in which the fibrous carbon precursor is heated to a high temperature to obtain fibrous carbon.

[0109] Next, each step will be described.

[0110] <Forming process> In the molding step, a mesophase pitch composition consisting of a thermoplastic resin and, preferably, 1 to 150 parts by mass of mesophase pitch per 100 parts by mass of the thermoplastic resin, is molded in a molten state to convert the mesophase pitch into fiber, thereby obtaining a resin composite fiber.

[0111] In order to produce ultrafine carbon fibers with an average fiber diameter of 10 to 900 nm, it is preferable that the dispersion diameter of the mesophase pitch in the thermoplastic resin is 0.01 to 50 μm. If the dispersion diameter of the mesophase pitch in the thermoplastic resin is out of the range of 0.01 to 50 μm, it may be difficult to produce the desired fibrous carbon. In the mesophase pitch composition, the mesophase pitch forms spherical or elliptical island components, and the dispersion diameter in the present invention means the diameter of the island components when they are spherical, and means the major axis diameter when they are elliptical.

[0112] The mesophase pitch composition can be produced by kneading a thermoplastic resin and a mesophase pitch in a molten state, for example, at a temperature of 100 to 400° C. The melt kneading of the thermoplastic resin and the mesophase pitch can be carried out using a known device. For example, one or more types selected from the group consisting of a single-screw kneader, a twin-screw kneader, a mixing roll, and a Banbury mixer can be used.

[0113] <Mesophase pitch> Mesophase pitch is a pitch that can form an optically anisotropic phase (liquid crystal phase) in a molten state. Examples of mesophase pitches used in the present invention include those made from coal or petroleum distillation residues, and those made from aromatic hydrocarbons such as naphthalene. For example, mesophase pitch derived from coal can be obtained by a process that mainly involves hydrogenation and heat treatment of coal tar pitch, or a process that mainly involves hydrogenation, heat treatment, and solvent extraction.

[0114] The optical anisotropy content (mesophase ratio) of the mesophase pitch is preferably 80% or more, and more preferably 90% or more.

[0115] The softening point of the mesophase pitch is preferably from 100 to 400°C, and more preferably from 150 to 350°C.

[0116] <Thermoplastic resin> The thermoplastic resin must be able to maintain its shape in the stabilization step and be easily removed in the step of obtaining a fibrous carbon precursor mixture, which will be described later. As such a thermoplastic resin, for example, polyolefin, polyacrylate polymers such as polymethacrylate and polymethyl methacrylate, polystyrene, polycarbonate, polyarylate, polyester, polyamide, polyester carbonate, polysulfone, polyimide, polyetherimide, polyketone, polylactic acid, etc. are preferably used. Among these, polyolefins such as polyethylene, polypropylene, poly-4-methylpentene-1, and copolymers containing these are preferably used.

[0117] The thermoplastic resin used in the present invention preferably has a glass transition temperature of 250° C. or lower if amorphous, and a melting point of 300° C. or lower if crystalline, in order to facilitate melt-kneading with the mesophase pitch.

[0118] <Resin composite fiber> An example of a method for producing a resin composite fiber from the above-mentioned mesophase pitch composition is a method in which the mesophase pitch composition is melt-spun from a spinneret. This can increase the initial orientation of the mesophase pitch contained in the resin composite fiber. The initial orientation can affect the fiber diameter and fiber length of the finally obtained fibrous carbon.

[0119] The average single fiber diameter of the resin composite fiber is preferably 10 to 200 μm. If it exceeds 200 μm, it becomes difficult for the reactive gas to come into contact with the mesophase pitch dispersed inside the resin composite fiber during the stabilization process described below. This reduces productivity. On the other hand, if it is less than 10 μm, the strength of the resin composite fiber may decrease, resulting in a decrease in process stability.

[0120] The temperature when producing (spinning) a resin composite fiber from a mesophase pitch composition must be higher than the melting temperature of the mesophase pitch, and is preferably 150 to 400° C. If the temperature exceeds 400° C., the deformation relaxation rate of the mesophase pitch increases, making it difficult to maintain the fiber shape.

[0121] The resin composite fiber obtained through these steps is in a state in which the mesophase pitch is micro-dispersed in the thermoplastic resin during kneading.

[0122] <Stabilization process> The resin composite stabilized fiber can be produced by contacting the above-mentioned resin composite fiber with a reactive gas containing oxygen. By contacting the reactive gas, the mesophase pitch contained in the resin composite fiber is stabilized (made infusible).

[0123] In this step, a stabilization step is carried out in which the mesophase pitch is stabilized by contacting the resin composite fiber with an oxygen-containing gas, such as air.

[0124] In the stabilization step, the reactive gas may contain an oxidizing gas other than oxygen or an inert gas. Examples of the oxidizing gas include nitrogen dioxide, nitric oxide, and sulfur dioxide, and examples of the inert gas include carbon dioxide, nitrogen, and argon. The preferred oxygen concentration is 0.1 to 21% by volume, although it varies depending on the type of mesophase pitch and the fiber diameter of the resin composite fiber.

[0125] According to the present invention, mesophase pitch is stabilized in a state of a resin composite fiber composited with a thermoplastic resin, and therefore process stability is not impaired even if the fiber diameter of the mesophase pitch is reduced, as compared with the case of stabilizing a fiber obtained by melt spinning only mesophase pitch.

[0126] During stabilization, the treatment can be carried out, for example, in a temperature range of 25 to 400° C. for 10 minutes to 10 hours.

[0127] <Removal process> The thermoplastic resin is removed from the resin composite stabilized fiber to obtain a fibrous carbon precursor. Methods for decomposing and removing the thermoplastic resin include, for example, a method for removing the thermoplastic resin using a solvent, and a method for removing the thermoplastic resin by thermal decomposition at, for example, 350 to 600°C. Among these, the method for removing the thermoplastic resin using a solvent has a problem that a large amount of the solvent is required and that the solvent must be recovered, resulting in an increase in process costs. Therefore, the latter method of removal by thermal decomposition is practical and preferable.

[0128] When the thermoplastic resin is removed by thermal decomposition, it may be carried out under reduced pressure. By thermal decomposition under reduced pressure, the thermoplastic resin can be removed more efficiently.

[0129] <High temperature heating process> The fibrous carbon can be obtained by heating a fibrous carbon precursor under an inert gas atmosphere to carbonize or graphitize the fibrous carbon precursor. This process affects the crystal structure of the fibrous carbon, and in particular, can adjust the distance between the graphite sheets (d002), the crystallite size (Lc002), the electrical conductivity (the powder volume resistivity), and the compression recovery.

[0130] Examples of the inert gas used in the high-temperature heating step include nitrogen and argon. The oxygen concentration in the inert gas is preferably 20 ppm by volume or less. The heating and sintering temperature during carbonization and / or graphitization is preferably 500 to 3500° C. The heating time is preferably 0.1 to 24 hours.

[0131] The container used in the high-temperature heating step may be made of metal, ceramic, or graphite depending on the heating temperature, but a graphite crucible is preferred.

[0132] (4-2) Carbon-based conductive additives other than fibrous carbon Examples of carbon-based conductive assistants other than fibrous carbon include carbon black, acetylene black, scaly carbon, graphene, and graphite. These carbon-based conductive assistants may be used alone or in combination of two or more.

[0133] The shape of these carbon-based conductive assistants is not particularly limited, but spherical particles such as carbon black and acetylene black are preferred. The average particle size (primary particle size) of the carbon-based conductive assistant is preferably 10 to 200 nm, more preferably 20 to 100 nm. The aspect ratio of these carbon-based conductive assistants is 10 or less, preferably 1 to 5, more preferably 1 to 3. The content of the carbon-based conductive assistant other than fibrous carbon in the active material layer of the present invention is preferably 0.1 to 4 mass % relative to the active material layer, more preferably 0.5 to 3 mass %, and even more preferably 1 to 2 mass %.

[0134] When the conductive assistant contains the above-mentioned fibrous carbon and the spherical particles, from the viewpoint of achieving both electronic conductivity and ionic conductivity, the mass ratio of the fibrous carbon is preferably 20% by mass or more and 99% by mass or less, and the mass ratio of the spherical particles is preferably 1% by mass or more and 80% by mass or less. More preferably, the mass ratio of the fibrous carbon is 40% by mass or more and 99% by mass or less, and the mass ratio of the spherical particles is 1% by mass or more and 60% by mass or less. The lower limit of the mass ratio of the fibrous carbon is preferably 50% by mass or less, more preferably 60% by mass or less, more preferably 70% by mass or less, more preferably 80% by mass or less, and particularly preferably 85% by mass or less. The upper limit of the mass ratio of the spherical particles is preferably 50% by mass or more, more preferably 40% by mass or more, more preferably 30% by mass or more, more preferably 20% by mass or more, and particularly preferably 15% by mass or more. It is believed that the small amount of spherical particles also acts as a cushion to buffer the volume change of the active material caused by repeated charge-discharge cycles.

[0135] (5) A method for manufacturing an active material layer for an all-solid-state lithium secondary battery The active material layer of the present invention can be produced, for example, by preparing a slurry by mixing the above-mentioned active material, solid electrolyte, conductive assistant, etc., and a solvent. This slurry is applied to a current collector by coating or the like, and then the solvent is dried to remove, and if necessary, pressure-molded by a press. Alternatively, the active material layer can be produced by mixing the above-mentioned active material, solid electrolyte, conductive assistant, etc. in powder form, and then pressure-molding by a press.

[0136] (6) All-solid-state lithium secondary battery An all-solid-state lithium secondary battery has the above-mentioned positive electrode active material layer, a solid electrolyte layer made of a solid electrolyte, and the above-mentioned negative electrode active material layer, in which the positive electrode active material layer and the negative electrode active material layer are arranged to sandwich the solid electrolyte layer. Usually, a positive electrode current collector is provided on the positive electrode active material layer, and a negative electrode current collector is provided on the negative electrode active material layer to sandwich them, and a battery case is arranged to cover all of them.

[0137] The all-solid-state lithium secondary battery of the present invention is not particularly limited as long as it has at least an active material layer and a solid electrolyte layer, and typically has a positive electrode current collector, a negative electrode current collector, a battery case, and the like, as described above.

[0138] In an all-solid-state lithium secondary battery, the active material layer and the solid electrolyte layer do not need to have a clear interface. If there is no clear interface, a layer in which 10% by volume or more of active material is present within 10 μm in the thickness direction can be regarded as the active material layer. EXAMPLES

[0139] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Various measurements and analyses in the examples were carried out according to the following methods.

[0140] (Confirmation of the shape of fibrous carbon) The effective fiber length and the fiber length of the fibrous carbon were measured by dispersing the fibrous carbon (sample) in 1-methyl-2-pyrrolidone and dispersing the dilute dispersion with an image analysis particle size distribution analyzer (Model IF-200nano, manufactured by Jusco International Co., Ltd.). The average effective fiber length and the average fiber length of the fibrous carbon are average values ​​based on the volume. The fiber diameter of the fibrous carbon was observed and photographed using a scanning electron microscope (S-2400 manufactured by Hitachi, Ltd.), 300 points were randomly selected from the obtained electron microscope photographs to measure the fiber diameter, and the average value of all the measurement results (n=300) was taken as the average fiber diameter. The CV value was calculated from the average value and the standard deviation. Furthermore, the average aspect ratio was calculated from the average effective fiber length and average fiber diameter.

[0141] (X-ray diffraction measurement of carbon fiber) X-ray diffraction measurements were performed using Rigaku RINT-2100 in accordance with JIS R7651, and the lattice spacing (d002) and crystallite size (Lc002) were measured.

[0142] (Method for measuring powder volume resistivity) The powder volume resistivity was measured using a four-probe electrode unit under a load of 0.02 to 2.50 kN using a powder resistivity system (MCP-PD51) manufactured by Mitsubishi Chemical Analytech Co., Ltd. The volume resistivity was measured at a packing density of 0.8 g / cm3 from the relationship diagram of the volume resistivity with respect to the change in packing density. 3 and 0.5g / cm 3 The volume resistivity value at this time was taken as the powder volume resistivity of the sample.

[0143] (Method for measuring compression recovery) The compression recovery was measured using a four-probe electrode unit under a load of 0.02 to 0.40 kN using a powder resistivity system (MCP-PD51) manufactured by Mitsubishi Chemical Analytech Co., Ltd. The compression recovery was calculated from the volume resistivity when the sample was compressed and the volume resistivity when the sample recovered after the compression was released (compression recovery (%) = volume resistivity at recovery / volume resistivity at compression × 100). The volume resistivity when compressed was obtained by calculating the change in volume resistivity at 0.1 MPa and 1.0 MPa from the relationship diagram of the volume resistivity with the change in pressure when the load was applied from 0.02 to 0.40 kN. The volume resistivity when recovered was obtained by calculating the change in volume resistivity at 0.1 MPa and 1.0 MPa from the relationship diagram of the volume resistivity with the change in pressure when the load was released from 0.40 kN to 0.02 kN.

[0144] (Method of measuring specific surface area) The specific surface area was measured using a specific surface area measuring device (Tristar II 3020) manufactured by Shimadzu Corporation in accordance with the method defined in JIS Z8830, and the specific surface area was calculated according to the BET formula.

[0145] (Mesophase pitch manufacturing method) The coal tar pitch with a softening point of 80°C from which the quinoline insoluble matter had been removed was hydrogenated in the presence of a Ni-Mo catalyst at a pressure of 13 MPa and a temperature of 340°C to obtain a hydrogenated coal tar pitch. This hydrogenated coal tar pitch was heat-treated at 480°C under normal pressure, and then the pressure was reduced to remove the low boiling point components to obtain a mesophase pitch. This mesophase pitch was filtered using a filter at a temperature of 340°C to remove foreign matter in the pitch, and a refined mesophase pitch was obtained.

[0146] (Production method of fibrous carbon (CNF) (i)) A mesophase pitch composition was prepared by melt-kneading 60 parts by mass of linear low-density polyethylene (EXCEED (registered trademark) 1018HA, manufactured by ExxonMobil, MFR = 1 g / 10 min) as a thermoplastic resin and 40 parts by mass of mesophase pitch (mesophase ratio 90.9%, softening point 303.5°C) obtained by (method of manufacturing mesophase pitch) in a co-rotating twin-screw extruder ("TEM-26SS" manufactured by Toshiba Machine Co., Ltd., barrel temperature 300°C, under nitrogen gas flow). The mesophase pitch composition was then formed into long fibers having a fiber diameter of 90 μm by a melt spinning machine using a circular die having a diameter of 0.2 mm and an introduction angle of 60°. The die temperature was 360° C., the discharge amount per spinning hole was 16.8 g / die / hour, and the draft ratio, which is the ratio of the discharge linear velocity to the take-up speed, was 5. 0.1 kg of the mesophase pitch-containing fiber bundle obtained by the above operation was used and held in air at 215°C for 3 hours to stabilize the mesophase pitch, thereby obtaining a stabilized mesophase pitch-containing fiber bundle. The stabilized mesophase pitch-containing fiber bundle was subjected to nitrogen replacement in a vacuum gas replacement furnace, then reduced in pressure to 1 kPa, and heated to 500°C at a heating rate of 5°C / min under the reduced pressure, and held at 500°C for 1 hour to remove the thermoplastic resin, thereby obtaining a stabilized fiber. The stabilized fiber was then carbonized by holding at 1000° C. for 30 minutes in a nitrogen atmosphere, and further graphitized by heating to 1500° C. in an argon atmosphere and holding for 30 minutes. The graphitized carbon fiber aggregate was then pulverized to obtain a powdered carbon fiber aggregate. The carbon fibers had a linear structure with no branches.

[0147] The obtained carbon fiber had no branching confirmed by SEM photographs (the branching degree was less than 0.01 / μm). The crystallite plane spacing d002 was 0.3441 nm, the crystallite size Lc002 was 5.4 nm, the average fiber diameter was 270 nm, the average effective fiber length was 90 μm, the CV value of the fiber diameter was 56%, the CV value of the effective fiber length was 83%, the average fiber length was 136 μm, the average aspect ratio was 333, the average effective fiber length / average fiber length ratio was 0.657, and the fiber length was 0.5 g / cm. 3The powder volume resistivity at is 0.0677 Ω cm and 0.8 g / cm 3 The powder volume resistivity is 0.0277 Ω cm, the compression recovery is 59%, and the specific surface area is 10 m 2 / g. The metal content was less than 20 ppm. The obtained carbon fiber was an excellent fibrous carbon with a large d002, a large aspect ratio, a long effective fiber length, and high electrical conductivity. Hereinafter, this fibrous carbon may be abbreviated as "CNF(i)".

[0148] (Method of manufacturing solid electrolyte (LPS)) Li2S and P2S5 were mixed in a molar ratio of 75:25 and subjected to ball milling (100 cycles of 12 minutes of rotation at 500 rpm followed by 8 minutes of rest) to produce a sulfide-based solid electrolyte (LPS). Hereinafter, this sulfide-based solid electrolyte may be abbreviated as "LPS."

[0149] Spherical particles: Acetylene black (hereinafter sometimes abbreviated as "AB"; "Denka Black" (registered trademark), manufactured by Denka Co., Ltd., 75% pressed product, average particle size: 0.036 μm, specific surface area: 65 m 2 / g)

[0150] <Example 1> (Method of producing positive electrode mixture) In an argon atmosphere, 36 parts by mass of LPS, 62 parts by mass of a positive electrode active material, and 2 parts by mass of fibrous carbon (CNF(i)) were mixed in an agate mortar. 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (average particle size: 10.18μm, D 50 : 10.26μm, Powder electrical conductivity: 5.46×10 -7 @2.47g / cm 3 hereinafter abbreviated as "NCM") was used.

[0151] (Electrical conductivity in the film thickness direction of the positive electrode active material layer) The positive electrode mixture prepared as described above was placed in an electrical conductivity measurement cell, and the electrical conductivity in the film thickness direction was measured while applying 100 MPa from above and below. The results are shown in Table 1.

[0152] (Method of manufacturing cells for evaluating all-solid-state batteries) A solid electrolyte layer was formed by filling a cell container for evaluating all-solid-state batteries with 10 parts by mass of LPS and pressing it three times at 100 MPa. One part by mass of a positive electrode mixture was added, pressed three times at 100 MPa, and left to stand for 30 seconds to form a positive electrode active material layer on one side of the solid electrolyte layer. Li foil (thickness 47 μm) and In foil (thickness 50 μm) were set as negative electrode active materials on the opposite side of the solid electrolyte layer, pressed at 80 MPa, and finally the cell was bolted to produce an all-solid-state battery evaluation cell in which a pressurized state of 8 N was maintained. The thicknesses of the positive electrode active material layer and the solid electrolyte layer were as shown in Table 1.

[0153] (Density and volume ratio of active material layer) The density of the active material layer was calculated from the total weight of the compositions in the active material layer and the volume of the active material layer. The volume ratio of each composition in the active material layer was calculated from the true density and filling amount of each composition and the volume of the active material layer, and the remaining volume was calculated as void.

[0154] (Density and porosity of solid electrolyte layer) The density and porosity of the solid electrolyte were calculated from the mass of the filled solid electrolyte and the volume of the solid electrolyte.

[0155] (First charge / discharge measurement) Using the cell prepared as described above, an initial charge / discharge measurement test was carried out at 70° C. The charge / discharge conditions were 0.05 C constant current charging up to 3.7 V, constant voltage charging for 4 hours, and 0.05 C constant current discharging down to 2.0 V. The charge capacity, discharge capacity, and charge / discharge efficiency are shown in the table.

[0156] (Rate characteristic evaluation) The discharge rate characteristics were measured using a cell that had been charged and discharged one cycle as described above. The charge and discharge tests were always carried out at 70°C. The conditions for measuring the discharge rate characteristics were as follows: The charging conditions were a constant current charge of 0.05C up to 3.7V, followed by discharging. The discharging conditions were a constant current discharge at each discharge rate with the lower limit voltage set to 2.0V. The discharge rate was increased stepwise from 0.1C to 0.2C to 0.5C to 1C. The discharge capacity (mAh / g) per weight of active material at each discharge rate is shown in the table. The larger the discharge capacity, the higher the output of the all-solid-state lithium secondary battery.

[0157] (AC impedance measurement) The AC impedance of each cell was measured using a potentiostat / galvanostat (VersaSTAT4 manufactured by Princeton Applied Research). The measurements were always carried out at 70°C. For the measurements, similar to the discharge rate characteristics, a pre-cycle was carried out using a charge / discharge device, and the cells were used in a charged state. The reaction resistance (Ω) of each cell is shown in the table. The lower the reaction resistance, the higher the output of the all-solid-state lithium secondary battery, which has both electronic conductivity and ionic conductivity.

[0158] <Example 2> The same procedure as in Example 1 was repeated, except that 1.6 parts by mass of CNF(i) and 0.4 parts by mass of AB were used instead of 2 parts by mass of CNF(i) in Example 1.

[0159] <Example 3> The same procedure as in Example 1 was repeated, except that 1 part by mass of CNF(i) and 1 part by mass of AB were used instead of 2 parts by mass of CNF(i) in Example 1.

[0160] <Comparative Example 1> The same procedure as in Example 1 was repeated except that 2 parts by mass of AB was used instead of 2 parts by mass of CNF(i) in Example 1.

[0161] <Example 4> The same procedures as in Example 1 were carried out except that the electrical conductivity in the thickness direction of the positive electrode active material layer in Example 1 (the pressing pressure was changed from 100 MPa to 500 MPa) and the method of producing an all-solid-state battery evaluation cell (the pressing pressure after adding the positive electrode composite was changed from 100 MPa to 500 MPa) were changed.

[0162] <Example 5> The same procedure as in Example 4 was repeated, except that 1.6 parts by mass of CNF(i) and 0.4 parts by mass of AB were used instead of 2 parts by mass of CNF(i) in Example 4.

[0163] <Example 6> The same procedure as in Example 4 was repeated, except that 1 part by mass of CNF(i) and 1 part by mass of AB were used instead of 2 parts by mass of CNF(i) in Example 4.

[0164] <Comparative Example 2> The same procedure as in Example 4 was repeated except that 2 parts by mass of AB was used instead of 2 parts by mass of CNF(i) in Example 4.

[0165] <Example 7> The positive electrode mixture was prepared in the same manner as in Example 1, except that the method was changed as follows. In an argon atmosphere, 35 parts by mass of LPS, 60 parts by mass of a positive electrode active material, and 5 parts by mass of CNF(i) were mixed in an agate mortar. 1 / 3 Co 1 / 3 Mn 1 / 3 O2(D 50 : 10.26 μm) was used.

[0166] <Example 8> The same procedure as in Example 7 was repeated, except that 4 parts by mass of CNF(i) and 1 part by mass of AB were used instead of 5 parts by mass of CNF(i) in Example 7.

[0167] <Example 9> The same procedure as in Example 1 was carried out, except that the surface of the positive electrode active material was coated with LiNbO3 (sometimes referred to as "surface-coated NCM").

[0168] (Method of producing fibrous carbon (CNF(ii))) Except for changing the graphitization temperature to 1700°C, carbon fibers were obtained in the same manner as in the production method of the fibrous carbon (CNF(i)) described above. The obtained carbon fiber had no branching confirmed by SEM photographs (the degree of branching was less than 0.01 / μm). The crystallite plane spacing d002 was 0.3432 nm, the crystallite size Lc002 was 8.7 nm, the average fiber diameter was 326 nm, the average effective fiber length was 81 μm, the CV value of the fiber diameter was 56%, the CV value of the effective fiber length was 80%, the average fiber length was 117 μm, the average aspect ratio was 248, the average effective fiber length / average fiber length ratio was 0.696, and the fiber density was 0.5 g / cm. 3 The powder volume resistivity at is 0.0602 Ω cm and 0.8 g / cm 3 The powder volume resistivity is 0.0205 Ω cm, the compression recovery is 73%, and the specific surface area is 9 m 2 / g. The obtained carbon fiber had a large d002 but a large aspect ratio, a long effective fiber length, and was an excellent fibrous carbon with high electrical conductivity. Hereinafter, this fibrous carbon may be abbreviated as "CNF(ii)".

[0169] <Example 10> LiNi as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (average particle size: 7.14μm, D 50 The procedure was the same as in Example 4, except that CNF(ii) was used instead of CNF(i), and CNF(ii) was used instead of CNF(i).

[0170] From the results of Example 3 and Example 6, it is found that, although the mass ratio of each member constituting the active material layer is the same, Example 3 has a small reaction resistance and good rate characteristics. In other words, it is suggested that a porosity of 9 volume % or more is more preferable, and it is presumed that the voids buffer the volume change accompanying the expansion and contraction of the active material accompanying the charge and discharge reaction.

[0171] From the results of Examples 1 to 3 and Comparative Example 1, it can be seen that the inclusion of fibrous carbon as a conductive additive results in low reaction resistance and good rate characteristics. It is suggested that the conductive path is maintained even if a volume change occurs due to the expansion and contraction of the active material accompanying the charge and discharge reaction, and it is presumed that this is the effect of the fibrous carbon forming a long-distance conductive path.

[0172] From the results of Examples 4, 5, and 6 and Comparative Example 2, in the case of the active material layer formed at a pressing pressure of at least 500 MPa, the porosity increases with an increase in the content of fibrous carbon. It is presumed that the fibrous carbon contributes to the maintenance and formation of voids when the pressing pressure is high.

[0173] [Table 1]

[0174] [Table 2]

[0175] [Table 3]

Claims

1. An active material layer for an all-solid-state lithium secondary battery, comprising at least an active material, a conductive assistant, and a solid electrolyte, the active material layer has voids, and the porosity is 5.0 vol.% or more and 42 vol.% or less; The proportion of the conductive assistant in the active material layer is 0.1% by mass or more and less than 5.0% by mass, The conductive assistant contains fibrous carbon having an average fiber diameter of 10 to 900 nm and an average effective fiber length of 10 to 200 μm, and the proportion of the fibrous carbon in the conductive assistant is 20 mass % or more.

2. The electrical conductivity of the active material layer in the thickness direction is 1.0×10 -3 2. The active material layer for an all-solid-state lithium secondary battery according to claim 1, wherein the active material layer has a specific surface area of ​​1.5 S / cm or more.

3. 3. The active material layer for an all-solid-state lithium secondary battery according to claim 1, wherein a volume ratio of the conductive assistant in the active material layer is 0.5 volume % or more and 4.0 volume % or less.

4. 4. The active material layer for an all-solid-state lithium secondary battery according to claim 1, wherein a volume ratio of the fibrous carbon in the active material layer is 0.5 volume % or more and 4.0 volume % or less.

5. The active material layer for an all-solid-state lithium secondary battery according to claim 1 , wherein the conductive assistant comprises the fibrous carbon and spherical particles.

6. 6. The active material layer for an all-solid-state lithium secondary battery according to claim 1, wherein the crystallite plane spacing (d002) of the fibrous carbon measured by an X-ray diffraction method is 0.3400 nm or more.

7. 7. The active material layer for an all-solid-state lithium secondary battery according to claim 1, wherein the coefficient of variation of the effective fiber length of the fibrous carbon is 35% or more and 90% or less.

8. The carbon fiber has the following formula (1): Compression recovery rate (%) = volume resistivity at recovery / volume resistivity at compression × 100 ... formula (1) 8. The active material layer for an all-solid-state lithium secondary battery according to claim 1, wherein the compression recovery rate represented by the following formula is 50% or more and 90% or less.

9. The specific surface area of ​​the conductive assistant is 1 m 2 / g or more 50m 2 The active material layer for an all-solid-state lithium secondary battery according to claim 1 , wherein the active material layer has a molecular weight of 1 / g or less.

10. The active material layer for an all-solid-state lithium secondary battery according to claim 1 , wherein the active material and the conductive assistant satisfy the following formula (2): Σ(Xe / Re) / Σ(Xa / Ra)<9...Formula (2) Xe: Content (mass%) of the conductive assistant contained in the active material layer, Re: average particle diameter (average fiber diameter) (μm) of the conductive assistant contained in the active material layer, Ra: average particle size (μm) of the active material contained in the active material layer, Xa: Content (% by mass) of active material contained in the active material layer

11. An all-solid-state lithium secondary battery comprising the active material layer according to claim 1 and a solid electrolyte.

Citation Information

Patent Citations

  • Slurry for forming positive-electrode mixture layer, and positive-electrode mixture layer

    JP2010262764A

  • All-solid-state lithium secondary battery

    JP2016009679A

  • Complex suitable for nonaqueous electrolyte secondary battery

    JP2016039146A

  • Method for manufacturing all-solid lithium ion secondary battery

    JP2018181706A

  • Bulk-type all-solid-state lithium secondary battery

    WO2016157348A1